2019
DOI: 10.1111/jir.12615
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype comparison among individuals with developmental delay/intellectual disability with or without genomic imbalances

Abstract: Background The chromosomal microarray analysis (CMA) is recommended as a first‐tier test for individuals with developmental delay (DD)/intellectual disability (ID) and/or multiple congenital anomalies. However, owing to high costs, this technique is not widely performed for diagnostic purposes in several countries. The aim of this study was to identify clinical features that could favour the hypothesis of genomic imbalances (GIs) in individuals with DD/ID. Methods The sample consisted of 63 individuals, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Among the 17 individuals in our study, pathogenic CNVs were found in four (23.5%), including the three previous imbalances found by MLPA at the 22q11.2 region, and CNVs classified as VOUS in other four (23.5%) individuals. These percentages are similar to those found in CMA studies of individuals with multiple congenital anomalies (de Souza et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Among the 17 individuals in our study, pathogenic CNVs were found in four (23.5%), including the three previous imbalances found by MLPA at the 22q11.2 region, and CNVs classified as VOUS in other four (23.5%) individuals. These percentages are similar to those found in CMA studies of individuals with multiple congenital anomalies (de Souza et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The interpretation of the chromosomal imbalances was based on international recommendations, according to the protocol developed by the FCM/UnicampCytogenetics and Cytogenomics Laboratory. 23 , 24 All CNVs were compared with data derived from the international databases: the Database of Genomic Variants (DGV), Affymetrix Database of Genomic Variants (aDGV), Database of Chromosomal Imbalance and Phenotype in Humans using Ensembl Resources (DECIPHER), Clinical Genome Resource (ClinGen), and Online Mendelian Inheritance in Man (OMIM). Cases with pathogenic and possibly pathogenic CNVs were classified as abnormal CMA, and those with normal CMA that included CNVs were classified as benign, possibly benign, or as a variation of unknown significance (VOUS).…”
Section: Methodsmentioning
confidence: 99%
“…The data were analyzed using the Affymetrix ® Chromosome Analysis Suite (ChAS) version 4.0 (Thermo Fisher Scientific Inc.—Life Technologies, Carlsbad, CA, USA). The interpretation and classification of copy number variants (CNVs) and regions of homozygosity (ROH) were performed as previously described [ 13 , 14 ] following recommendations from the American College of Medical Genetics and Genomics(ACMG) [ 15 ] and the European guidelines for constitutional cytogenomic analysis [ 16 ]. The percentage of homozygosity in the patient’s autosomal genome was calculated by the sum of all homozygous regions detected (excluding the sex chromosomes), divided by total autosomal length, and multiplied by 100 [ 17 ] after using fixed detection settings.…”
Section: Methodsmentioning
confidence: 99%